Application of rules of transportation planning based on principles of transport justice developed by Karel Martens in Windhoek - Nashilongo, Mweneni (Department of Civil Engineering, 2021)
Transportation planning over the years focused on providing mobility for car users. The focus on mobility has left people who cannot afford automobiles without access to different activities within their societies. The lack of access, in turn, resulted in social exclusion. In the book ‘Transport Justice' Martens showed that the distinct social meaning of the transport good lies in the accessibility. And therefore, accessibility should be the focus of transportation planning to mitigate lack of access and in turn social exclusion. Moreover, Martens developed principles of justice for transportation planning which focuses on identifying groups of people experiencing accessibility shortfalls to help planners focus resources towards those people who are socially excluded due to inadequate transportation systems. This paper aimed to use the principles of justice for transportation planning to identify population groups experiencing insufficient accessibility in the City of Windhoek by assessing potential mobility and accessibility in the city. Additionally, the paper aimed to evaluate how well the rules apply to a small city with a different land use and transport system to the Amsterdam case study from the book ‘Transport Justice'. To assess the transport system, the population of Windhoek was divided into groups based on location, income, and modal split. The accessibility levels and potential mobility levels for each population group per mode were then determined using four accessibility measures and the Potential Mobility Index (PMI-score). The groups were then assigned under 50%, 30%, and 10% accessibility thresholds based on their respective accessibility levels. Under each threshold, groups that contributed the most to the unfairness of the transportation system were identified and ranked based on their respective Accessibility Fairness Index scores (AFI). The results showed that most public transport dependent population groups contributed to the Windhoek transportation system unfairness. These groups are located in Havana, Okuryangava, Wanaheda, and Goreangab at the fringes of the city with low-income residents. Even with limited data, the application of the principles to Windhoek yielded an insightful overview of accessibility in within the city that showed gross inequalities in accessibility to jobs between the car owners and public transport users and between low income and high income earners. The application of the principles of justice for transportation planning produced comprehensible insight on the effects of the transportation system on accessibility to employment in Windhoek. The insight has shown that theory and principles developed by Martens can be useful in the African context where there are significant disparities in accessibility.